IDENTIFIKASI BAHAYA DAN PENILAIAN RISIKO PADA PENYAPU JALAN DI DINAS LINGKUNGAN HIDUP KOTA BALIKPAPAN - zainul, L.M. Zainul; Maslina, Maslina; Nugraha, Agung (IDENTIFIKASI, 2021)
Street sweepers in carrying out their work are very vulnerable to various risks, especially safety and health risks such as the risk of hearing loss due to noise, stress, dehydration, being hit by a vehicle, as well as health problems due to fatigue, bacteria, respiratory system disorders caused by inhaling dust and vehicle fumes. The purpose of the study was to determine the dangers and conduct an assessment of the safety and health risks of workers and to find out the control efforts that have been made to road sweepers. The research methodology used is descriptive qualitative. In conducting risk identification and assessment using the Hazard Identification Risk Assessment and Risk Control (HIRARC) standard AS/NZS 4360 method. The total risk level is 27 categories with details of 7 (seven) Low risk levels, 15 (fifteen) Medium risk levels, and 5 (five) levels of High risk. After controlling for each existing risk using the OHSAS 18001 guidelines, namely elimination, substitution, engineering control, administration, PPE (Personal Protective Equipment). After the risk is handled with the hierarchy of control, the assessment is carried out again on the remaining risks of control with the results of the study on 27 risks down to 22 low risks and 5 medium risks. Keywords: Hazard, Hazard Identification Risk Assessment and Risk Control (HIRARC), Risk.